CORPORAL PUNISHMENT, SELF-CONTROL, PARENTING STYLE, AND SCHOOL BULLYING AMONG CHINESE ADOLESCENTS: A CONDITIONAL PROCESS ANALYSIS. (2nd January 2022) - Liu, Weidi; Qiu, Geping; Zhang, Sheldon X.; Fan, Qi
ABSTRACT: Research on generational transmission of violence suggests that parental corporal punishment in Western countries often leads to violent behavior among children. Violence begets violence, to most Western childrearing scholars. However, the socio-cultural context within which corporal punishment is administrated matters and often produces unexpected consequences. Utilizing a sample (N = 2, 075) from six middle schools in central China, we employed a series of conditional process analysis to assess the mediating effect of self-control and moderating effect of parenting style in the relations of corporal punishment and physical bullying. Our findings show that parental corporal punishment was not always associated with physical bullying in school. Its impact on physical bullying was moderated by the parenting style within which it is applied. Authoritative parenting would protect children from elevated physical bullying perpetration even when they were physically punished. Self-control mediated the relations of corporal punishment and physical bullying only among boys raised by rejecting parenting and girls raised by indulgent and rejecting parenting. These findings suggest that cultural and parental contexts need to be considered in the exploration of impacts of corporal punishment on child development. Implications for practice and directions of future research are discussed.